The Complete Letters of Constance Fenimore Woolson - Dean, Sharon L., 1943- (Book collections on Project MUSE., 2012)
In recent years Constance Fenimore Woolson (1840-1894) has been fictionalized at least three times, perhaps most notably in Colm Tóibín's award-winning work The Master, a novelization of the life of Woolson's close friend Henry James. But Woolson was a literary star in her own right, publishing in the premier magazines of her day. She penned critically acclaimed novels, short stories, and poetry until her mysterious death in Venice at age fifty-three. Sharon Dean has recompiled, dated, and, in many cases, physically reassembled all of Woolson's extant correspondence from nearly forty sources.